The association between maternal overprotection and idol worship among college students: the chain mediating role of reactive anger and cybervictimization - Li, Yaoyao; Wang, Xiaogang; Zhang, Ludan; Chen, Liang (Frontiers in Psychology, 2025)
IntroductionAs a unique socio-cultural phenomenon, idol worship plays a significant role in the development of college students' ideological and moral values. This study aims to investigate the influence of maternal overprotection on idol worship and examine the mediating roles of reactive anger and cybervictimization.MethodsA total of 847 Chinese college students (23.50% were male; Mage = 19.57, SDage = 1.25) were investigated in this cross-sectional survey from 7 to 12 January in 2024 by S-EMBU-C questionnaire, celebrity attitude scale (CAS-R), trait anger scale (TAS), and cybervictimization questionnaire, testing the chain mediating effects of reactive anger, and cybervictimization.Results and conclusion(1) Maternal overprotection significantly positively predicted idol worship; (2) Cybervictimization played an independent mediator role in the links between maternal overprotection and idol worship; (3) Reactive anger and cybervictimization played a chain mediating role between maternal overprotection and idol worship. These findings highlighted the association between maternal overprotection and idol worship among college students, highlighting the need for integrated interventions targeting parenting styles, and online safety.